Patent Law: Balancing Profit Maximization and Public Access to Technology - Beckerman-Rodau, Andrew (Science and Technology Law Review, 2019)
This article addresses the contemporary issue of balancing the need for patent protection for intellectual property with the resulting restriction of public access to new technology. The author argues that patent law protects private property rights rather than creating monopolies. Additionally, the author discusses how restricting access to patented technology, such as pharmaceuticals, can affect public health problems, such as the HIV/AIDS epidemic in developing nations. The author then concludes with some proposals for making patented technology available to people in developing nations who need access to such technology but who are unable to afford its high costs due to patent protection.